Emergent Challenges and Opportunities to Sustaining Age-friendly Initiatives: Qualitative Findings from a Canadian Age-friendly Funding Program. Issue 2 (4th March 2022) - Russell, Elizabeth; Skinner, Mark W.; Fowler, Ken
ABSTRACT: Age-friendly initiatives often are motivated by a single funding injection from national or sub-national governments, frequently challenging human and financial resources at the community level. To address this problem, this paper examines the challenges and opportunities to sustaining age-friendly programs in the context of a Canadian age-friendly funding program. Based on a qualitative thematic content analysis of interview data with 35 age-friendly committee members drawn from 11 communities, results show that age-friendly sustainability may be conceptualized as an implementation gap between early development stages and long-term viability. Consistent over-dependence on volunteers and on committees' limited capacity may create burnout, limiting sustainability and the extent to which communities can truly become "age-friendly". To close this implementation gap while still remaining true to the grass-roots intention of the global age-friendly agenda, sustainable initiatives should include community champions, multi-disciplinary and cross-sector collaborations, and systemic municipal involvement.